Long-term cardiac changes in patients with systemic lupus erythematosus - De Godoy, Moacir Fernandes; De Oliveira, Cibele Matsuura; Fabri, Vanessa Alves; De Abreu, Luiz Carlos; Valenti, Vitor E [UNESP]; Pires, Adilson Casemiro; Raimundo, Rodrigo Daminello; Figueiredo, José Luiz; Bertazzi, Glauce Rejane Leonardi (Springer Nature, 2013)
Background: The aim of this study was evaluate the late-onset repercussions of heart alterations of patients with systemic lupus erythematosus (SLE) after a 13-year follow up. Methods. A historical prospective study was carried out involving the analysis of data from the charts of patients with a confirmed diagnosis of lupus in follow up since 1998. The 13-year evolution was systematically reviewed and tabulated to facilitate the interpretation of the data. Results: Forty-eight patient charts were analyzed. Mean patient age was 34.5 ± 10.8 years at the time of diagnosis and 41.0 ± 10.3 years at the time of the study (45 women and 3 men). Eight deaths occurred in the follow-up period (two due to heart problems). Among the alterations found on the complementary exams, 46.2% of cases demonstrated worsening at reevaluation and four patients required a heart catheterization. In these cases, coronary angioplasty was performed due to the severity of the obstructions and one case required a further catheterization, culminating in the need for surgical myocardial revascularization. Conclusion: The analysis demonstrated progressive heart impairment, with high rates of alterations on conventional complementary exams, including the need for angioplasty or revascularization surgery in four patients. These findings indicate the need for rigorous cardiac follow up in patients with systemic lupus erythematosus. © 2013 de Godoy et al.; licensee BioMed Central Ltd.
Keywords: Cardiovascular diseases; Lupus erythematosus systemic